PENGARUH PELATIHAN PEMBIDAIAN TERHADAP KESIAPAN ANGGOTA PMR SMA 5 KETAHUN DALAM MELAKUKAN PENANGANAN AWAL FRAKTUR - Bardah Wasalamah; Desi Susilawati; Yusran Hasymi; Nova Yustisia (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2023)
Accidents that happened at school are very diverse. One result of an accident can cause fracture. It is a problem that requires serious handling. Participation of members of the Youth Red Cross or other students to provide initial treatment before being handled by health workers is very important. One way to increase student readiness in first aid in accidents is by providing training. Splint dressing training is the initial handling of fractures that can be given to students to increase knowledge, attitudes, and skills in dealing with injuries/trauma due to fractures. The aim of study is to determine the effect of Splint Dressing Training on readiness (knowledge, attitude, and skills of Youth Red Cross (PMR) Students at SMA 5 Bengkulu Ketahun. This study used pre-experiment with one group pretest posttest design. Population in this study were students of Youth Red Cross (PMR) during 2022 in SMA 5 Ketahun with the amount of 21 students. Sample consists of 21 respondents using a total sampling technique. Data analysis in this study used univariate and bivariate with Uji Wilcoxon Signed Rank Test to compare the results of the pretest and posttest. The result of study showed that based on the Wilcoxon Signed Rank Test obtained p-value (Sig. 2-tailed) of 0.000 < α (0.05). There was an increase in mean value of readiness (knowledge, attitudes, and skills) after being given splint dressing training. The mean value of knowledge (80.95), attitude (89.52), and skills (92.04), so that can be concluded there is effect of Splint Dressing Training to readiness of Youth Red Cross (PMR) Students at SMA 5 Ketahun. It is expected that SMA 5 Ketahun can collaborate with Indonesian Red Cross, Public health center, and the authorities regarding the first treatment of injuries, so can help students making efforts to deal with students who experience injuries at school.